2012
DOI: 10.6061/clinics/2012(09)03
|View full text |Cite
|
Sign up to set email alerts
|

Etiological diagnosis reduces the use of antibiotics in infants with bronchiolitis

Abstract: OBJECTIVE:Acute bronchiolitis is a leading cause of infant hospitalization and is most commonly caused by respiratory syncytial virus. Etiological tests are not required for its diagnosis, but the influence of viral screening on the therapeutic approach for acute bronchiolitis remains unclear.METHODS:A historical cohort was performed to assess the impact of viral screening on drug prescriptions. The study included infants up to one year of age who were hospitalized for bronchiolitis. Virus screening was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
(23 reference statements)
0
24
0
2
Order By: Relevance
“…Although molecular assays represent the gold standard for diagnosing viral ARI, nucleic acids of respiratory viruses in asymptomatic individuals have been demonstrated (Jansen et al, 2011). Furthermore, as NAATs are usually associated with longer response time and higher costs, the use of point-of-care antigen detection methods in healthcare settings have demonstrated clinical benefits (Benito-Fernández et al, 2006;D'Heilly et al, 2008;Ferronato et al, 2012). Rapid detection of viral respiratory pathogens is also important for taking appropriate isolation measures of confirmed cases in order to prevent nosocomial outbreaks, especially during Flu and RSV epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although molecular assays represent the gold standard for diagnosing viral ARI, nucleic acids of respiratory viruses in asymptomatic individuals have been demonstrated (Jansen et al, 2011). Furthermore, as NAATs are usually associated with longer response time and higher costs, the use of point-of-care antigen detection methods in healthcare settings have demonstrated clinical benefits (Benito-Fernández et al, 2006;D'Heilly et al, 2008;Ferronato et al, 2012). Rapid detection of viral respiratory pathogens is also important for taking appropriate isolation measures of confirmed cases in order to prevent nosocomial outbreaks, especially during Flu and RSV epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid etiological diagnosis of ARI improves patients' management, as it allows for appropriate and on-time antiviral therapy, which has demonstrated a reduction of complications, duration of symptoms, and hospital stay (D'Heilly et al, 2008;Fiore et al, 2011). Indeed, rapid diagnosis avoids the use of unnecessary antibiotics and ancillary diagnostic studies (Ferronato et al, 2012;Benito-Fernández et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Because concurrent serious bacterial infection with RSV is uncommon, especially in children (6), a timely diagnosis of RSV ARI should diminish unnecessary antibiotic use (7)(8)(9). It may also minimize ancillary testing (10), decrease hospital stay durations (11), and permit prompt implementation of cohort assignment for the purpose of limiting nosocomial transmission within hospitals and long-term-care facilities (13)(14)(15)(16)57).…”
Section: 01) Our Results Suggest That the Poor Sensitivity Of Rsv mentioning
confidence: 99%
“…Even though multiplex PCR assays can detect several different viruses simultaneously and rapidly, their advantages in terms of cost reduction over other rapid diagnostic assays (DFA, antigen detection) are still unclear. When rapid antigenic diagnostic tests for viral infections became widely used, several studies demonstrated their clinical utility in reducing length of hospital stay, performance of ancillary diagnostic tests and antibiotic consumption among pediatric (Bonner et al, 2003;Esposito et al, 2003;Sharma, 2002;Woo et al, 1997) (Abanses et al, 2006;Benito-Fernández et al, 2006;Byington et al, 2002;Ferronato et al, 2012;Iyer et al, 2006;Noyola & Demmler, 2000) and adult (Barenfanger et al, 2000;D'Heilly et al, 2008;Falsey et al, 2007) populations. Their cost-effectiveness was also shown with both populations (Barenfanger et al, 2000;Woo et al, 1997).…”
Section: Cost-effectivenessmentioning
confidence: 99%